2019
DOI: 10.1111/evj.13136
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic vs. autologous intra‐articular mesenchymal stem cell injection within normal horses: Clinical and cytological comparisons suggest safety

Abstract: Summary Background Allogeneic bone marrow‐derived mesenchymal stem cells (BMDMSCs) could provide multiple advantages over autologous BMDMSCs, including creating an ‘off‐the‐shelf’ treatment together with the ability to control for donor variation. Objectives The objective of the study was to compare the clinical and synovial fluid response of the normal equine joint to autologous and pooled‐allogeneic BMDMSCs while controlling for individual variation and joint variations in response to intra‐articular injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…In fact, at a single time point (6 hours) post‐injection, an increase in subjective lameness was appreciated in both the AUTO‐ and ALLO‐treated groups compared to horses treated with rIL‐1β alone. Although not substantiated by objective lameness data, this result is consistent with previous studies of intra‐articular administration which found that BMDMSCs may result in an inflammatory effect . A single previous study in horses evaluated the use of umbilical‐derived MSCs in a lipopolysaccharide (LPS)‐induced inflammatory joint model.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, at a single time point (6 hours) post‐injection, an increase in subjective lameness was appreciated in both the AUTO‐ and ALLO‐treated groups compared to horses treated with rIL‐1β alone. Although not substantiated by objective lameness data, this result is consistent with previous studies of intra‐articular administration which found that BMDMSCs may result in an inflammatory effect . A single previous study in horses evaluated the use of umbilical‐derived MSCs in a lipopolysaccharide (LPS)‐induced inflammatory joint model.…”
Section: Discussionsupporting
confidence: 88%
“…Because of this, treatments directed against IL‐1β, such as IL‐1β receptor antagonist protein, have resulted in improved clinical outcomes and disease‐modifying effects . Although BMDMSCs have been increasingly used as an anti‐inflammatory joint therapy, intra‐articular administration has been found to result in an inflammatory response in normal joints . Furthermore, no studies have investigated the effect of BMDMSCs in an inflammatory model of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in order to improve the feasibility of using these in the clinic, we chose to evaluate MSCs derived from the same recipient donor (autologous) or another donor (allogeneic) [34]. Autologous MSCs have a less immunologic reaction; however, using these MSCs has proven to be costly and time-consuming in vitro [17]. While allogeneic MSCs have the advantage to offer an "offthe-shelf" therapy, their safety must be well established before clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Data also indicate that exposing MSCs to synovial fluid might alter their chondrogenesis phenotype and, as a result, the response of MSCs to synovial fluid is not consistent. In equines, autologous and allogeneic MSCs can be used for the treatment of musculoskeletal disorders [17], modifying inflammatory processes [18] and have demonstrated no adverse immunological reactions to intra-articular injection [19]. Therefore, the first aim of our study is designed to determine the survival rate and chondrogenic effects of autologous and allogenic synovial fluid on equine BMMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the immunogenicity, safety, and efficacy of exosomes from xenogeneic and allogenic sources have not been fully characterized, numerous preclinical studies have made such evaluations in cellular therapies. With studies showing disease improvement in both allogeneic and autologous treatments, it is promising that pre-clinical studies using exosomes from such cellular sources would better overcome regulatory hurdles when translated to a clinical setting [48,74,75]. Since some exosome studies have shown unaffected differentially expressed genes related to inflammation or toxicity, as well as no visual signs of toxicity after repeated administration, exosome therapies show promise [76,77].…”
Section: Exosome Therapeuticsmentioning
confidence: 99%